ВИКОРИСТАННЯ ПРИНЦИПІВ ГУМАНІЗМУ В СОЦІАЛЬНІЙ РОБОТІ - YAREMCHUK, Serhii; HNATCHUK, Oksana; SHESTAKOVA, Kateryna (My University, 2022)
The article shows that the satisfaction of humanitarian problems in social work contributes to a fuller realization of human disclosure in society, especially in times of transformation of social values at the stage of creating a "consumer society". In the process of social work is the formation of life and moral and ethical values due to the interaction of the individual and society, which is the highest value, as it is about human life, protecting it from crisis situations. However, the progress of society, the creation of social conditions under which full realization would take place, the disclosure of man is possible only through the satisfaction of humanitarian problems. In the process of social work, both vital and moral and ethical values are formed. The axiological function of social work is mainly manifested in the interaction of employee and client, as well as in cooperation between social workers and social services. The highest value of social work is recognized by the International Code of Ethics for Social Workers, as social work is based on various humanistic, religious and democratic ideals and philosophical theories and is a universal opportunity to meet human needs arising from human and social interactions and human potential. Person of the modern world easily changes activities, interests, beliefs, values, which leads to a spiritual crisis. This crisis is caused not only by global processes, but also by internal issues, including social protection, when a person is unable to respond quickly to change, loses habitual social behavior and finds himself in a stressful or difficult life situation (unemployment, illness, homelessness, refugee status, etc.). Supporting a person in such a situation, helping to find meaning in life, raising self-esteem, adaptation to new social conditions will largely depend on the professional behavior of social workers, their correct interaction with those in difficult situations. Practical activity in this case will be to recognize the biological, psychological, social and spiritual aspects of human life, understanding them as whole individuals.
USE OF PRINCIPLES OF HUMANISM IN SOCIAL WORK
Keywords: humanism; social work; ethical norms; spirituality; morality